PEMERIKSAAN DNA SENTUHAN DARI BARANG BUKTI DENGAN PERBEDAAN JENIS BAHAN - vira saamia; I MADE WIRANATHA; irfan rofik; setia betaria aritonang; Dwi Ana Oktaviani (Pusat Laboratorium Forensik adan Reserse Kriminal Kepolisian Negara Republik Indonesia, 2021)
Analysis of Touch DNA on forensic laboratory has been a favorite approach to identify a person. Every investigator demand the identity of whom the perpetrator that commit the crime, that leaved their DNA on the evidence. Many factors affect touch DNA, one of these is the substrate of the evidence. Common evidences that often examined in forensic lab are firearms, knife, swords, clothes, and switch bomb. To collect the cell on the evidence we use tapelift method using the duct tape. PrepFilerTM BTA Extraction Kit used to extract the DNA from the duct tape, followed by Quantifiler® Duo. For profiling the DNA we use GlobalFilerTM and fragment analyzed on ABI 3500 Genetic Analyzer followed by GeneMapper ID.X. V.1.4. Based on our analysis, DNA from fabric substrate has the higher percentage of success DNA profiling. The success DNA profiling rate of fabric and plastic substrate is 100%, and 0% for wood substrate. According to recent researches, smooth substrate, like plastic and glass, has higher percentage to get full profile than rough substrate, like woods. But on the fabric, they found has much higher percentage than smooth substrate. This can be due to the absorption ability of the fabric to obtain more cells